Weissella ceti sp. nov., isolated from beaked whales (Mesoplodon bidens) - Vela Alonso, Ana Isabel; Fernández Rodríguez, Antonio Jesús; Bernaldo De Quirós Miranda, Yara; Herráez Thomas, Pedro Manuel; Domínguez Rodríguez, Lucas; Fernández-Garayzabal Fernández, José Francisco (International Journal of Systematic and Evolutionary Microbiology, 2011)
During an investigation into the microbiota of beaked whales (Mesoplodon bidens), nine isolates were obtained from different organs of four animals. The isolates were Gram-positive-staining, catalase-negative, short rod-shaped or coccoid organisms. A phylogenetic analysis based on 16S rRNA gene sequences of these isolates allocated them to the genus Weissella, showing 96.3% and 96.0% 16S rRNA gene sequence similarity with Weissella viridescens NRIC 1536(T)and Weissella minor NRIC 1625(T), respectively. On the basis of phenotypic, physiological and phylogenetic evidence, it is proposed that the new isolates from whales represent a novel species of the genus Weissella, Weissella ceti sp. nov. The type strain of Weissella ceti is 1119-1A-09(T) (=CECT 7719(T)=CCUG 59653(T)). 2762 2758 1,09 2,268 Q1 Q3 SCIE